Student-run free clinics (SRFC) can solve three problems for Pakistan - Ahmad, Bashir; Wazir, Rabia (Journal of the Pakistan Medical Association, 2025)
Madam, Student-run free clinics are primary care bodies run by medical schools where students provide care under the supervision of senior faculty. SRFCs serve three main purposes in society i.e. undergraduate education, primary care and social justice providing care to the socially deprived. (1) It adds an extra layer of primary care and lessens the burden on secondary and tertiary care hospitals. In the United States, more than 75% of institutions are running SRFCs which provide care in chronic disease management, specialty care, imaging, laboratories, pharmaceuticals, and interdisciplinary services. (2) Care provided at these clinics is at par with other primary health care facilities. (3) They are equally important as a tool of undergraduate medical education (UME) as well as a social justice initiative. Considering Pakistan’s current economic status, SRFCs appear as an option worth trying. These free clinics if reasonably funded, could save thousands of dollars for Pakistan’s healthcare system. Such clinics will help monitor chronically ill patients and will be more cost effective as compare to advanced care units. According to the International Diabetes Federation, Pakistan is ranked third highest in number of diabetic cases. (4) These free clinics can reduce the burden by monitoring and providing necessary care to the diabetic population. Depending on the capabilities of the parent institution, the SRFC can provide care in various other areas as well. The SRFCs can serve as a potentially viable training ground for future doctors. Students from academically advanced years can be assigned different types of work at the clinics. Even first and 2nd-year students can be engaged in history taking and vitals monitoring whereas 3rd and 4th-year students can perform clinical examinations and interpretation of lab reports. Fifth year and interns can work under the direct supervision of senior faculty to prescribe medicine, perform minor procedures and lead other junior colleagues as well. This approach could foster a culture of collegiality, leadership, peer-assisted learning (PAL), and community involvement and at the end of all improve students’ clinical skills and confidence in patient management. Students managing such clinics will also get hands-on experience in running a healthcare setup and dealing with governance and legal issues. Advocacy and social justice in medicine can be encouraged using such initiatives. Students who work at these clinics will be introduced to public health, social work, global health initiatives and the importance of primary health care. ---Continue